Pengembangan Kuliner Tradisional Lengkong Kecil Sebagai Daya Tarik Wisata Kota Bandung - Khoirul Fajri; Zia Kemala (STIEPAR YAPARI Bandung, 2022)
This research is about the development of traditional culinary in the Lengkong sub-district as a tourist attraction. This research is expected to be able to explore local wisdom as traditional culinary to innovate into contemporary traditional culinary, so as to increase tourist attraction in the city of Bandung. The method used in this research is using descriptive qualitative method. The data collection techniques used in this study were observation, interviews and documentation studies. This study has several key informants, namely traditional food sellers in Lengkong Kecil, Head of Lengkong Tourism Activists (PWL), Head of RW 01 to Head of RW 04, Paledang Village, Lengkong District, Paledang Village Head and Lengkong Sub-District Head. The first step is conduct field observations and then to deepen the data, interviews are conducted. After obtaining sufficiently complete data, a documentation study was carried out to strengthen the data that had been collected. Based on the results of the analysis of tourist attraction through fulfilling the indicators of what to see, what to do, what to buy, what to arrive and what to stay, Lengkong Kecil traditional culinary has good potential. Meanwhile, from the SWOT analysis, alternative development strategies can be carried out through an aggressive strategy by maximizing opportunities to increase strength so that it can be concluded that alternative strategies and strategic priorities can be applied to the development of Lengkong Kecil traditional culinary.